Profilin as a regulator of the membrane-actin cytoskeleton interface in plant cells - Sun, Tiantian; Li, Shanwei; Ren, Haiyun (Frontiers in Plant Science, 2013)
Membrane structures and cytoskeleton dynamics are intimately inter-connected in the eukaryotic cell. Recently, the molecular mechanisms operating at this interface have been progressively addressed. Many experiments have revealed that the actin cytoskeleton can interact with membranes through various discrete membrane domains. The actin-binding protein, profilin has been proven to inhibit actin polymerization and to promote F-actin elongation. This is dependent on many factors, such as the profilin/G-actin ratio and the ionic environment of the cell. Additionally, profilin has specific domains that interact with phosphoinositides and poly-L-proline rich proteins; theoretically, this gives profilin the opportunity to interact with membranes, and a large number of experiments have confirmed this possibility. In this article, we summarize recent findings in plant cells, and discuss the evidence of the connections among actin cytoskeleton, profilin and biomembranes through direct or indirect relationships.